Drosophila melanogaster as a model for nutrient regulation of ovarian function. Issue 2 (February 2020) - Armstrong, Alissa Richmond
Abstract : Observed in a wide variety of organism, from invertebrates to mammals, nutritional status modulates the energetically costly effort of producing female gametes. Despite this long-standing link between nutrition and ovarian function, relatively little is known about the cellular and molecular mechanisms that underlie how dietary components modulate egg production. Drosophila melanogaster, with its powerful and extensive genetic tools as well as its well-characterized ovarian response to diet, has proven to be instrumental in addressing this issue. This review covers what we currently know about the dietary control of oogenesis in Drosophila and the salient features of the fruit fly that make it a model for nutritional control of ovarian function.